2006
DOI: 10.1243/09544070jauto319
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian Risk from Cars and Sport Utility Vehicles - A Comparative Analytical Study

Abstract: Analysis of real-world crash data from the USA shows that 11.5 per cent of pedestrians struck by large sport utility vehicles (SUVs) are killed, compared with 4.5 per cent of pedestrians struck by passenger cars. The design of the vehicle front-end structure has a substantial influence on injury outcome when pedestrians are struck by vehicles. In the context of the rising population of SUVs, it is important to determine the causes of their increased hazard to pedestrians. In this paper, validated multi-body mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 19 publications
1
33
1
Order By: Relevance
“…They concluded that the head injuries were similar or slightly lower from contact with SUVs compared to cars, but injuries to the mid-body regions were substantially higher. They analyzed that the primary reason for the increased hazard to pedestrians from SUVs is the high front shape of the bumper and bonnet, and the mass difference between cars and SUVs is not very significant for pedestrian injury causation [23]. The point where their results meet ours is their prediction or suggestion that lowering the bumper and bonnet and reducing the bonnet stiffness for SUVs would help reduce injuries to these mid-body regions.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…They concluded that the head injuries were similar or slightly lower from contact with SUVs compared to cars, but injuries to the mid-body regions were substantially higher. They analyzed that the primary reason for the increased hazard to pedestrians from SUVs is the high front shape of the bumper and bonnet, and the mass difference between cars and SUVs is not very significant for pedestrian injury causation [23]. The point where their results meet ours is their prediction or suggestion that lowering the bumper and bonnet and reducing the bonnet stiffness for SUVs would help reduce injuries to these mid-body regions.…”
Section: Discussionmentioning
confidence: 67%
“…It is calculated from the resultant head acceleration (measured in g) like (4), where time is measured in seconds, and the maximum time interval is 36 ms. In (4), a head denotes the resultant head acceleration in g unit, and t 1 and t 2 denote the impact starting and ending times, respectively [23]. The HIC has many shortcomings, but an HIC of 1000 has been associated with a 50% risk of skull fracture [24].…”
Section: Pedestrian Injury Criterionmentioning
confidence: 99%
“…The model is validated using both literature sources (Ishikawa et al 1993;Kerrigan et al 2005;Simms & Wood, 2006;Stammen & Barsan-Anelli, 2001) involving experiments with PMHS (Post Mortem Human Subject) and dummies, and also, in several cases, using computer simulations of performed tests. As a key source the work of Kerrigan et al (2005), presenting the detailed description of the experiment with a full-scale pedestrian impact, is chosen.…”
Section: External Experimental Backgroundmentioning
confidence: 99%
“…Despite the precise description of the test itself, the publication lacks detailed information about the car material characteristics. Hence additional literature sources (Simms & Wood, 2006;Stammen & Barsan-Anelli, 2001) are used to complete the model parameters. The car is modeled as rigid with parameters defined according to a real small car, as reported in Table 1.…”
Section: Impact Scenario Setupmentioning
confidence: 99%
See 1 more Smart Citation